Performance of 18F-DCFPyL PET/CT Imaging in Early Detection of Biochemically Recurrent Prostate Cancer: A Systematic Review and Meta-Analysis - Sun, Jiale; Lin, Yuxin; Wei, Xuedong; Ouyang, Jun; Huang, Yuhua; Ling, Zhixin (Frontiers in Oncology, 2021)
Background: Prostate-specific membrane antigen (PSMA) targeted 18F-DCFPyL positron emission tomography/computed tomography (PET/CT) has shown advantages in primary staging, restaging and metastasis detection of prostate cancer. However, little is known about the role of 18F-DCFPyL PET/CT in biochemically recurrent prostate cancer (BRPCa). Hence, we performed a systematic review and meta-analysis to evaluate 18F-DCFPyL PET/CT as first-line imaging modality in early detection of BRPCa. Methods: A comprehensive literature search of PubMed, Web of Science, Embase, Cochrane Library was conducted until December 2020. The pooled detection rate on a per-person basis and together with 95% confidence interval (CI) was calculated. Furthermore, a prostate-specific antigen (PSA)-stratified performance of detection positivity was obtained to assess the sensitivity of 18F-DCFPyL PET/CT in BRPCa with different PSA levels. Results: A total of 9 eligible studies (844 patients) were included in this meta-analysis. The pooled detection rate (DR) of 18F-DCFPyL PET/CT in BRPCa was 81% (95% CI: 76.9-85.1%). The pooled DR was 88.8% for PSA ≥ 0.5 ng/mL (95% CI: 86.2-91.3%) and 47.2% for PSA < 0.5 ng/mL (95% CI: 32.6–61.8%). We also noticed that the regional lymph node was the most common site with local recurrence compared with other sites (45.8%, 95% CI: 42.1-49.6%). Statistical heterogeneity and publication bias were found. Conclusion: The results suggest that 18F-DCFPyL PET/CT has a relatively high detection rate in BRPCa. The results also indicate that the imaging with 18F-DCFPyL may exhibit improved sensitivity in BRPCa with increased PSA levels. Considering the publication bias, further large-scale multi-center studies are warranted for validation.